Stress-induced core temperature changes in pigeons (Columba livia) - Bittencourt, Myla de Aguiar; Melleu, Fernando Falkenburger; Marino-Neto, José (Physiology & behavior, 2015)
Changes in body temperature are significant physiological consequences of stressful stimuli in mammals and birds. Pigeons (Columba livia) prosper in (potentially) stressful urban environments and are common subjects in neurobehavioral studies; however, the thermal responses to stress stimuli by pigeons are poorly known. Here, we describe acute changes in the telemetrically recorded celomatic (core) temperature (Tc) in pigeons given a variety of potentially stressful stimuli, including transfer to a novel cage (ExC) leading to visual isolation from conspecifics, the presence of the experimenter (ExpR), gentle handling (H), sham intracelomatic injections (SI), and the induction of the tonic immobility (TI) response. Transfer to the ExC cage provoked short-lived hyperthermia (10–20min) followed by a long-lasting and substantial decrease in Tc, which returned to baseline levels 2h after the start of the test. After a 2-hour stay in the ExC, the other potentially stressful stimuli evoked only weak, marginally significant hyperthermic (ExpR, IT) or hypothermic (SI) responses. Stimuli delivered 26h after transfer to the ExC induced definite and intense increases in Tc (ExpR, H) or hypothermic responses (SI). These Tc changes appear to be unrelated to modifications in general activity (as measured via telemetrically recorded actimetric data). Repeated testing failed to affect the hypothermic responses to the transference to the ExC, even after nine trials and at 1- or 8-day intervals, suggesting that the social (visual) isolation from conspecifics may be a strong and poorly controllable stimulus in this species. The present data indicated that stress-induced changes in Tc may be a consistent and reliable physiological parameter of stress but that they may also show stressor type-, direction- and species-specific attributes. •Social isolation prompts biphasic (hyper- and hypo-) thermal response in pigeons•Short-lived early hyperthermia is evoked by handling and tonic immobility•Long-lasting late hypothermia is expressed after sham intracelomatic injection•Social isolation-induced hypothermia does not habituate to repeated testing•Thermal changes in pigeons may be stimulus-specific stress markers